2011
DOI: 10.2516/ogst/2011004
|View full text |Cite
|
Sign up to set email alerts
|

Have We Overestimated Saline Aquifer CO2Storage Capacities?

Abstract: Résumé -Avons-nous surestimé les capacités de stockage de CO 2 des aquifères salins ? -Au cours d'opérations à grande échelle de stockage géologique de CO 2 dans des aquifères salins, la pression des fluides dans les formations va augmenter, mais devra rester sous des limites définies par des contraintes d'intégrité des sites de stockage. La hausse de pression est la conséquence de deux effets distincts. Premièrement, la pression augmente localement autour des injecteurs de CO 2 pour permettre l'injection du C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Firstly, a local overpressure effect around the CO 2 injection wells, as a result of high CO 2 velocities created by injection. Increasing the number of injection wells and spacing them appropriately can control this albeit at additional expense 18 . Secondly, regional pressure build up from the inefficient displacement of water by the injected CO 2 , meaning that the volume of water being displaced is not enough to compensate for the volume of CO 2 injected 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, a local overpressure effect around the CO 2 injection wells, as a result of high CO 2 velocities created by injection. Increasing the number of injection wells and spacing them appropriately can control this albeit at additional expense 18 . Secondly, regional pressure build up from the inefficient displacement of water by the injected CO 2 , meaning that the volume of water being displaced is not enough to compensate for the volume of CO 2 injected 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Early research suggested that these had the capacity to store hundreds of years of CO 2 emissions 5 . These original estimates have now been downgraded, as they did not accurately take into account the fluid pressure increase which would result from the injected CO 2 18,19 . For storage security it is essential that the fluid pressure in a saline formation is not significantly raised to ensure that faults and fractures are not created or reactivated.…”
Section: Introductionmentioning
confidence: 99%
“…There are various values for suggested fracture pressure limits in the literature, and the allowable maximum pressure increase has to be assessed on a case-by-case basis (Thibeau and Mucha 2011); however, I present a simplistic approach where the fracture pressure is calculated by p fr,w (g f g h ) p t 0 h,i . Here, g f and g h are, respectively, the fracture gradient and the hydrostatic gradient of the geothermal system, and p t0 h,i is the initial hydrostatic pressure at gridblock i where the well w is perforated.…”
mentioning
confidence: 99%
“…A summary table in (Thibeau and Mucha, 2011) provides an overview, where estimated total capacity ranges from 0.3 Gt (Chadwick et al, 2008) to 20-60 Gt (Lindeberg et al, 2009). The large variation in published estimates is due to different assumptions made, in particular to what is considered the main limiting factors.…”
Section: Introductionmentioning
confidence: 99%
“…If the aquifer is considered closed, or with low hydraulic connectivity, then pressure buildup becomes the main concern. The estimates in (Lindeberg et al, 2009;Thibeau and Mucha, 2011) are based on the prevention of excessive pressure buildup, and the 60 Gt estimated figure from (Lindeberg et al, 2009) is arrived at by assuming extensive production of formation water to alleviate pressure buildup from CO 2 injection into a closed system. On the other hand, if the aquifer is considered open with good hydraulic connectivity, leakage risk due to long-term CO 2 migration typically becomes the main limiting factor on storage capacity.…”
Section: Introductionmentioning
confidence: 99%